2020
DOI: 10.1016/j.msea.2020.139276
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure influence on creep properties of heat-resistant austenitic alloys with high aluminum content

Abstract: This work focusses on the link between microstructure and creep properties for heat-resistant austenitic alloys with high aluminum content (3-5 wt. %). An emphasis was put on the coupling of thermodynamic simulations, microstructural characterizations by scanning electron microscopy and transmission electron microscopy, and creep testing. The phase predictions performed by the calculation of phase diagrams method are in good agreement with the observed microstructure after creep at 1000°C and 1050°C. Correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…They are surrounded by two kinds of carbides: Cr-rich M7C3 (darkly imaged) and (Nb,Ti)-rich MC (brightly imaged). More information on microstructures and phase identification in such alloys can be found in [10,39,40].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are surrounded by two kinds of carbides: Cr-rich M7C3 (darkly imaged) and (Nb,Ti)-rich MC (brightly imaged). More information on microstructures and phase identification in such alloys can be found in [10,39,40].…”
Section: Methodsmentioning
confidence: 99%
“…A first patent has been published in 1981 for an alloy based on HP grade [8], but the development was stopped due to creep resistance problems [9]. Better understanding of creep mechanisms in Al-containing austenitic stainless alloys up to 1000-1050°C [10] has contributed to develop a new generation of alloys for steam cracking applications. It has been shown indeed that 3 to 5 wt% of aluminum could be successfully added leading to the formation of an Al2O3 subscale.…”
Section: Introductionmentioning
confidence: 99%
“…They said that an increase in the solution treatment temperature could decrease secondary phase carbide precipitates, leading to abnormal grain growth. The findings of Facco et al 22 revealed that the great creep performance of FeNiCrAl alloys stems from the existence of secondary carbides and the absence of a step of NiAl. Considering that the NiAl stage does not remain an efficient dislocation movement barrier and a decrease of creep life is found.…”
Section: Microstructurementioning
confidence: 99%
“…Numerous reports [12][13][14][15][16][17][18][19][20][21][22][23] prove that by increasing the grain size, the creep rate will decrease or increase based on the experiment conditions, material properties, and role of the grain boundaries. For stainless steel, Lee et al 12 prove that as the grain size increases, the steadystate creep rate decreases to a minimum value and then increases from the intermediate grain size.…”
mentioning
confidence: 99%
See 1 more Smart Citation